GLOBALIZATION, COMMUNICATION, EDUCATION - Monica Condruz-Bacescu (Journal of Languages for Specific Purposes, 2018)
The paper focuses on the issues of globalization, communication and education. Globalization has become the fundamental theme of political discourse, through its economic dimension, namely by opening up the economic markets in search of new stability points of contemporary developed capitalism; a phenomenon that has led to the free movement of labor, thus involving the social dimension, the circle being closed with the educational dimension because the individual, regardless of the cultural context in which he/she lives, needs training. The global economy cannot be conceived without international communication, which has become a premise of economic success in recent decades. Such communication on which the economic partnerships and multinational organizations are based presupposes an accurate perception and interpretation of the different cultures other than those in which the economic activity takes place and a permanent negotiation of the symbols and reference systems. Education undoubtedly plays an important role in any attempt to address communication networks in these moments of explosive development, networks that mediate communication between people and can thereby help to bring them closer together. Education must directly follow the transformations and new requirements in order to support future changes and professional training. In this direction, education will have as an educational purpose the development of the consciousness of the links between the different components and participants, regardless of the geographic area in which they operate, and on this basis the building of the partnership. Education needs to efficiently and extensively convey that knowledge and information adapted to the new civilization of globalization that does not overwhelm but contribute to the development of people at individual and community level. It must also trace the transformations of the new world that is constantly moving, and at the same time make available to people the tools of guidance with which they can find their way of affirmation and continuous development.